Uji Organoleptik dan Kandungan Gizi Makro pada Makanan Jajanan Nugget Ikan Cakalang dengan Penambahan Ubi Ungu untuk Anak Sekolah - Galib, Siti Hijra; Dhesa, Desiderius Bela; Ihsan M, Habib; Ananda, Siti Hadrayanti; Demmalewa, Jenny Qlifianti; Abadi, Ellyani (Jurnal Gizi Ilmiah, 2023)
School age is a period that decides the event of good development and improvement. Admission of nutritious food is vital to guarantee the development and advancement of solid and dynamic kids. Along these lines, young kids are designated in further developing local area nourishment to plan quality next ages. This review plans to decide the organoleptic test and macronutrient content of skipjack fish chunk snacks with the expansion of purple yam for younger students in grades V and VI at Primary School 2 South Wawonii. This examination is a semi exploratory quantitative exploration, utilizing a totally randomized concentrate on plan, the review populace is 30 understudies. The examining procedure utilizes all out inspecting and is tried by Univariate. The outcomes showed that the healthful substance of skipjack fish chunks with the expansion of purple sweet potato was 23.47% in Piece R1, while in Chunk R2 it was 26.25%. .. The dietary substance of skipjack fish piece fat with the expansion of purple sweet potato was 12.38% in Chunk R1, while the R2 Chunk was 13.19%. The degree of inclination for smell, variety, surface, skipjack fish pieces with the expansion of purple yam in South Wawonii 2 Public Primary School understudies, the greater part of them preferred R1 chunks